Nitrate uptake by p-phosphonic acid or p-(trimethylammonium)methyl calix[8]arene stablized laminar materials - Eggers, P.; Eroglu, E.; Becker, Thomas; Chen, X.; Vimalanathan, K.; Stubbs, K.; Smith, S.; Raston, C. (Royal Society of Chemistry, 2014)
Graphite, BN, MoS2 and WS2 are readily exfoliated using probe sonication in the presence of p-(trimethylammonium)methyl-calix[8]arene resulting in few-layer laminarmaterial. The positively charged material is effective in the removal of nitrate ions from waste effluent, as is the negatively charged corresponding material stablized by partially deprotonated p-phosphonic acid calix[8]arene, with scope for efficient recycling.